Mechanisms of ferroptosis and targeted therapeutic approaches in lymphoma - Tiantian Yu; Zijun Y. Xu-Monette; Li Yu; Yong Li; Ken H. Young (Cell Death and Disease, 2023)
Abstract Lymphoma is the sixth most common type of cancer worldwide. Under the current treatment standards, patients with lymphoma often fail to respond to treatment or relapse early and require further therapy. Hence, novel therapeutic strategies need to be explored and our understanding of the molecular underpinnings of lymphomas should be expanded. Ferroptosis, a non-apoptotic regulated cell death, is characterized by increased reactive oxygen species and lipid peroxidation due to metabolic dysfunction. Excessive or lack of ferroptosis has been implicated in tumor development. Current preclinical evidences suggest that ferroptosis participates in tumorigenesis, progression, and drug resistance of lymphoma, identifying a potential biomarker and an attractive molecular target. Our review summarizes the core mechanisms and regulatory networks of ferroptosis and discusses existing evidences of ferroptosis induction for the treatment of lymphoma, with intent to provide a framework for understanding the role of ferroptosis in lymphomagenesis and a new perspective of lymphoma treatment.